2007
DOI: 10.1037/1076-8998.12.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Electronic diary evidence on energy erosion in clinical burnout.

Abstract: Burnout is generally defined as a state of severe exhaustion. So far, research has predominantly focused on relatively mild burnout in employees able to work despite their complaints. This study examines energy depletion in clinical burnout (e.g., the severest cases on extended sick leave) by comparing the diurnal patterns of fatigue and exhaustion with those of healthy individuals. Sixty clinically burned-out and 40 healthy participants kept an electronic diary for 14 days, 7 times a day, yielding a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…19), indicating that the association between burnout and injuries was not moderated by the time elapsed between the survey and injury, therefore justifying the use of proportional hazard models. The interaction effects between burnout and sex or age group on injuries were not statistically significant (p>0.32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19), indicating that the association between burnout and injuries was not moderated by the time elapsed between the survey and injury, therefore justifying the use of proportional hazard models. The interaction effects between burnout and sex or age group on injuries were not statistically significant (p>0.32).…”
Section: Resultsmentioning
confidence: 99%
“…About 30% of them are workrelated 21) . It also has been shown that burnt-out individuals suffer from severe fatigue throughout the day 19) and that burnout may spill over to other life domains 20) . Therefore, if the worker is burned out, he or she may be injured also outside the work domain, for example, during commutation, at home, or in leisure time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables under study were measured with singular diary items, according to the premises of the Experience Sampling Method (ie, items were to measure states instead of constructs and mimic an internal dialogue) and thus needed to be short and easy to comprehend (32). Exhaustion was defined as a severe and stable form of fatigue that is no longer responsive to normal periods of rest and emerges only when fatigue becomes chronic (33)(34)(35). Exhaustion was measured by the statement "Right now I feel exhausted".…”
Section: Methodsmentioning
confidence: 99%
“…Note that this sample has been used before in another different study on energy erosion and burnout (see : Sonnenschein, Sorbi, van Doornen, Schaufeli, & Maas, 2007).…”
Section: Participantsmentioning
confidence: 99%